Sources of Finance and Growth - Sugata Marjit; Pranab Kumar Das (CESifo GmbH, 2024)
The paper provides an analysis of the simultaneous existence of the formal and the informal sources of finance and their implications for the rate of growth in an economy. Our main result is that in the presence of two sources of borrowing, viz. formal banking sector with lower interest rate with finance constraint and an informal credit market with a higher interest rate but unlimited amount of availability of loans, the informal source may boost the rate of growth. Hence, without the informal source of finance easily the growth rate could have been lower. The premium associated with the differential interest rate in favour of the informal source unequivocally increases propensity towards investment. Thus higher interest rate in the informal source provides the incentive to save resources from from own production as banks do not lend beyond the quota. Thus, if diminishing returns do not impede marginal productivity too much, availability of informal credit must act as a growth stimulant. Thus the presence of informal credit market can be an effective catalyst for growth and development, contrary to what is generally perceived in the literature on financial inclusion.
Keywords: G20; O40; 330; finance; informal; growth